C.J.'s Fate - Hooper, Kay (Detroit, Mich. : Large Print Press, 2007)
A New York Times Bestselling Author. Before such New York Times bestselling thrillers as Blood Dreams and Sleeping with Fear Kay Hooper made her mark with novels blending romance and suspense. In this new edition of C.J.'s Fate, Hooper delivers a funny, sexy, heartfelt story about breaking free, taking chances - and finding the last thing you're looking for. Librarian C.J. Adams is content to stay single. History is her love, and few men compare with its daring heroes. But C.J.'s close friends disagree.
96500
Keywords: Women librarians; Large type books; Love stories